Death, Demography and the Denominator: New Influenza-18 Mortality Estimates for Ireland - Christopher L. Colvin; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2020)
Using the Irish experience of the Spanish flu, we demonstrate that pandemic mortality statistics are sensitive to the demographic composition of a country. We build a new demographic database for Ireland's 32 counties with vital statistics on births, ageing, migration and deaths. We then show how age-at-death statistics in 1918 and 1919 should be reinterpreted in light of these data. Our new estimates suggest the very young were most impacted by the flu. New studies of the economic impact of Influenza-18 must better control for demographic factors if they are to yield useful policy-relevant results. Covid-19 mortality statistics must go through a similar procedure so policymakers can better target their public health interventions.
Keywords: N34; I18; Q54; 330; demographic economics; pandemics; age-adjusted mortality; Spanish flu; Ireland